MoSe2 nanosheet/MoO2 nanobelt/carbon nanotube membrane as flexible and multifunctional electrodes for full water splitting in acidic electrolyte. Issue 19 (8th May 2018) - Yang, L. J.; Deng, Y. Q.; Zhang, X. F.; Liu, H.; Zhou, W. J.
Abstract : Porous, conductive and flexible membranes, composed of MoSe2 NSs, MoO2 NBs and CNTs, were successfully prepared and possessed remarkable electrocatalytic performance for full water splitting in acidic electrolyte. Abstract : Acid-stable and efficient hydrogen evolution reaction (HER) catalysts have been widely reported. However, achieving full water splitting catalysis in acidic electrolytes is still an urgent task due to the lack of efficient, abundant and acid-stable oxygen evolution reaction (OER) catalysts. This rationally designed MoSe2 nanosheet/MoO2 nanobelt/carbon nanotube membrane (MoSe2 NS/MoO2 NB/CNT-M) is composed of highly conductive CNTs and hierarchical MoSe2 nanosheets on MoO2 nanobelts, and due to its flexible three-dimensional (3D) electrodes, possesses an open architecture for rapid ion/electron diffusion, maximising the exposure of its active sites. The MoSe2 NS/MoO2 NB/CNT-M achieved remarkable electrocatalytic performance for the HER, providing a geometrical current density of 1 mA cm −2 at an onset potential of −23 mV vs. RHE, a small Tafel slope (69.4 mV dec −1 ) and excellent long-cycle stability in 0.5 M H2 SO4 . More importantly, the obtained multifunctional electrodes delivered excellent electrocatalytic activity towards the OER under acidic conditions, with a very small onset potential (≈+1.43 V vs. RHE) and enhanced long-cycle durability. The two-electrode electrolyzer, composed of a MoSe2 NS/MoO2 NB/CNT-M both as an anode and a cathode, required a small voltage of 1.63 V to achieve 10 mA cm −2 and improved electrocatalytic durability, which was better than that of an electrolyzer composed of RuO2 //20 wt% Pt/C. This work highlights the potential for active and abundant non-precious catalysts for full water splitting in acidic electrolytes.